PENGARUH KUALITAS KERJA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA PROGRAM STUDI AKUNTANSI UNIVERSITAS PAMULANG - Sri Nitta Crissiana Wirya Atmaja (Universitas Pamulang, 2019)
This study aims to obtain empirical evidence of the influence of work quality and service quality on the satisfaction of students of the Accounting study program at the University of Pamulang, Pamulang Banten, both partially and simultaneously.This study uses primary data in the form of a questionnaire. The sample collection technique uses purposive sampling. The research subjects were undergraduate accounting students in semester 8-14 at Pamulang University, by taking a sample of 100 respondents. Respondents' answers in the form of the questionnaire will be analyzed using multiple linear regression analysis techniques using SPSS 22.00 to be concluded.The results showed that work quality and service quality together affect student satisfaction. Partial testing concluded that work quality and service quality had a positive and significant effect on student satisfaction. Keywords: work quality, service quality, and student satisfaction